PREVENTION OF PROTEIN ADSORPTION ON BARE FUSED-SILICA CAPILLARY BY PEG IN CAPILLARY ZONE ELECTROPHORESIS - Adhitasari Suratman; Hermann Waetzig (Indonesian Journal of Chemistry, 2009)
The protein separation was studied in capillary zone electrophoresis for preventing protein adsorption on the capillary wall. ß-lactoglobulin (pI: 4.83-5.4, Mr: 18.4 kDa), cytochrome c (pI: 9.59, Mr: 11.7 kDa) and ß-casein (pI: 4.6, Mr: 24 kDa) were used as protein models. Strong adsorption of the proteins occurred onto the capillary at a pH around their pIs. In order to prevent protein adsorption, PEG (Poly(ethylene glycol)) was investigated as an effective substance to stabilize the proteins native state and coat the bare fused-silica capillary surface. The presence of 32 mg/mL PEG in buffer solution in a pH range of 6.0 to 4.0 was successful to suppress protein adsorption during the separation. It can also be confirmed with the reproducibility of apparent EOF mobility with percentile RSD (Relative Standard Deviation) less than 2% in long-term measurement.